The Effect of Lateral Box Jump Training with Front Box Jump Training on Leg Muscle Power in Futsal Athletes (Universitas Negeri Semarang, 2022)
Abstract. In the Futsal sport. Biomotor components such as leg power are one of the components that need to be considered by the trainer in compiling an exercise program, especially exercise in physical conditions. If the athlete can bring out the maximum leg power, the athlete can help the team win the match. So the coach must choose the right exercises to increase the strength of the athlete, one of which is plyometric exercises including the lateral box jump and front box jump. The research objective was to determine the effect of the lateral box jump and front box jump on leg power. The method used is qualitative research with an experimental approach. The subjects used were 20 athletes who participated in the futsal UKM UNIPA Surabaya. The results showed that the lateral box jump and front box jump had a significant effect on leg power, but the box jump training provided a greater increase in increasing leg muscle power.Abstract in Indonesia. Pada Futsal. Pelatih yang akan menyusun suatu program latihan harus memperhatikan komponen biomotorik, seperti power otot tungkai. Power otot tungkai sangat berpengaruh dalam kemenangan pertandingan sebuah tim jika seorang atlet dapat mengeluarkan power otot tungkai secara maksimal. Sehingga pelatih perlu pandai dalam memilih latihan yang sesuai dalam menaikkan power atlet, salah satunya latihan plyometric antara lain lateral box jump dan front box jump. Tujuan penelitian untuk mengetahui pengaruh lateral box jump dan front box jump terhadap power tungkai. Metode penelitian kualitatif dengan pendekatan eksperimen. Subjek penelitian ini sejumlah 20 atlet yang mengikuti UKM futsal UNIPA Surabaya. Hasil penelitian menunjukkan bahwa lateral box jump dan front box jump berpengaruh signifikan terhadap power otot tungkai, tetapi pada pelatihan front box jump memberikan peningkatan yang lebih besar dalam meningkatkan power otot tungkai.